Synthesis, herbicidal activity, and molecular simulation study of anethole-based 4-methyl-1,2,4-triazole-thioether compounds - Yucheng Cui; Chuwen Liu; Youqiong Bi; Xianli Ma; Wengui Duan; Guishan Lin (Phytochemistry Letters, 2026)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Construction of SiO2/porous DA-g-C3N4 composite nanofiltration membranes with high Mg2+/Li+ selectivity based on reverse interfacial polymerization - Xin Shi; Qiuyan Bi; Zizhen Peng; Zhicheng Wang; Yakai Lin; Wenzhong Ma; Chuanjie Fang; Chao Zhang; Shiai Xu (Desalination, 2026)

VolSur: Efficient surface reconstruction for geological volumes with distinct constraints - Deyun Zhong; Xingliang Xu; Liguan Wang; Zhaohao Wu; Lin Bi (Computers & Geosciences, 2026)

Potassium ferrate combined with cation exchange resin achieved efficient protein extraction from primary sludge - Ling Wang; Huan Liu; Jinbiao Zhu; Yan Wang; Lei Gao; Xiaoqiu Lin; Xuejun Bi; Heliang Pang (Biomass and Bioenergy, 2026)

Enhanced simultaneous nitrogen and phosphorus removal via a step-feed anoxic/oxic process coupled with side-stream enhanced biological phosphorus removal - Ruoyu Wu; Dongqi Wang; Mengbo Huang; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Wengui Gu; Lu Qin; Yuan Guo; Xiaopeng Qiu; Yishan Lin; Da Kang; et al. (Journal of Environmental Chemical Engineering, 2026)

Intermittent stirring-mediated solids retention time–hydraulic retention time decoupling enhances side-stream enhanced biological phosphorus removal performance and microbial selection - Yanzhe Gong; Dongqi Wang; Wengui Gu; Ruoyu Wu; Guangxiang Duan; Jiayu Bi; Xiaopeng Qiu; Yuan Guo; Yishan Lin; Hongfang Sun; Xi Wen; Chenxin Tang; et al. (Journal of Environmental Chemical Engineering, 2026)

Research on the regulation mechanism of CaO on NO formation during the co-combustion of sewage sludge and wheat straw - Zhanshi Ni; Qizhao Lin; Kesheng Meng; Chunlong Jiang; Haobo Bi (Journal of Environmental Chemical Engineering, 2026)

Experimental investigation on MILD combustion characteristics of NH3/CH4 blended fuels in a swirl combustion chamber - Junjian Tian; Haobo Bi; Chuanwen Lv; Gaofeng Wang; Qizhao Lin (Fuel, 2026)

Decoupling interface regulation and L-arginine interface empowerment to construct stable Mg2+/Li+ separation positively charged polyamide nanofiltration membranes - Xin Shi; Qiuyan Bi; Zizhen Peng; Zhicheng Wang; Fangbo Zhu; Yakai Lin; Wenzhong Ma; Chuanjie Fang; Shiai Xu (Chemical Engineering Journal, 2026)

Tailoring subnanometer transport pathways in polyamide nanofiltration membranes for high-permeance Li+/Mg2+ separation - Zhicheng Wang; Xin Shi; Zizhen Peng; Wenzhong Ma; Yakai Lin; Hideto Matsuyama; Qiuyan Bi (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Disentangling the role of sheet flow in sediment distribution heterogeneity across micro-topographic sloping farmland - Lin Chen; Ruijie Yang; Bo Bi; Qinqian Meng; Jie Lin; Jian Wang (Soil and Tillage Research, 2026)

Glass transition and crystallization behavior of jujube powders as induced by amorphous sugars based on solid model system - Yonghong Lin; Jinfeng Bi; Gege Liu; Qinqin Chen (Journal of Food Engineering, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Lead exposure in an urban population: isotopic evidence reveals contributions from dietary and inhalation pathways - Shuhui Mu; Jin Wu; Jiaxin Ye; Jiemin Liu; Guangle Qiu; Xiaoyuan Lin; Xiangyang Bi (Applied Geochemistry, 2026)

Establishment of a Neonatal Facial Phenotype Atlas for Genetic Disease Screening in a Retrospective Chinese Cohort - Jieyi Chen; Yunqian Zhu; Bi Ze; Huihui Chen; Chuan Li; Qi Ni; Yulan Lu; Liyuan Hu; Lin Yang; Bingbing Wu; Huijun Wang; Laishuan Wang; et al. (Phenomics, 2026)

BR signaling mitigates Cu toxicity in rice by integrating ROS homeostasis with copper translocation - Huaying Du; Lulu Sun; Quanlei Shentu; Jinglin Pan; Jing Bi; Zishen Liao; Xianhui Lin; Dongmei Chen; Rensen Zeng; Yuanyuan Song (Plant Science, 2026)

Single-walled carbon Nanotube-Encapsulated polyoxometalates for Wide-Range humidity PEM fuel cells - Chenyu Liu; Qinghao Lin; Jujia Zhang; Qin Liu; Xianglong Wan; Wentuan Bi (Fuel, 2026)

Halloysite surface-induced spin-state regulation and hydroxyl-assisted adsorption: A dual enhancement mechanism for PMS activation - Haiyi Lv; Sikai Zhao; Yan Li; Qiang Zhao; Xiaoyu Jiang; Hongshan Bi; Zhou Lin; Yanbai Shen (Chemical Engineering Journal, 2026)

Interatomic push-pull engineering in heterocyclic covalent organic frameworks for boosting photocatalytic hydrogen peroxide production - Wenjun Yang; Jialong Lv; Yuelin Chen; Weikang Peng; Shibin Zheng; Wei Lin; Jinhong Bi; Guocheng Huang (Chemical Engineering Journal, 2026)

A subcellular spatial profiling platform for expanding the drug toxicity window - Liu Yang; Qingjie Bai; Shuyuan Guo; Luyao Hu; Chenghao Bi; Litao Shao; Zihao Lin; Kairui Cui; Shenshen Yang; Jinxia Wei; Liwei Shao; Liwen Han; et al. (Chemical Engineering Journal, 2026)

TRIM9-Mediated Degradation of SMAD4 Promotes Pyroptosis and Disruption of the Endothelial Barrier in Aortic Dissection Disease - Hong-Qin Bi; Tan Yang; Sheng-Lin Ling; Feng-Xu Yu (Cardiovascular Toxicology, 2026)

Enhanced Monosaccharide Profile and Anti-Alcoholic Liver Injury Activity in the Liquid Fermentation of Ecklonia kurome by Inonotus hispidus - Baohong Wei; Xue Yang; Jia Liu; Wanghua Bi; Shaoping Wang; Shuman Hu; Xiaoqing Ma; Wenzhe Yang; Changyun Wang; Lin Ju; Huashi Guan (Journal of Ocean University of China, 2026)

VoxOct: A Sparse Voxel Framework for Large-Scale Geological Volume Representation - Deyun Zhong; Xingliang Xu; Zhaohao Wu; Binglei Li; Lin Bi; Liguan Wang (Natural Resources Research, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Electrochemical engineering in situ induces highly thermodynamically stable interface toward long-life zinc metal anodes - Min Lin; Le Zhang; Xijun Liu; Shuyu Bi; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Dual-configuration arabinogalactan-II synergizes with rhamnogalacturonan-I in Lycium barbarum pectin to construct an intestinal anti-inflammatory glycan scaffold - Guoqiang Li; Yajun Qiao; Qiannan Wang; Xingfang Zhang; Lin Rong; Lixin Wei; Tingting Gao; Hongtao Bi (Carbohydrate Polymers, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Morphology - seepage - stress coupling response of fractured rock mass MICP reinforcement under confining pressure: in-situ NMR reveals roughness threshold effect - Yongle Liu; Jing Bi; Lin Ning; Sheng Ren; Ziyang Zhao (Bulletin of Engineering Geology and the Environment, 2026)

Study on prestack reservoir prediction of deep volcanic rock gas reservoirs in Chaganhua sub-sag of Songnan Fault Depression - Qin-lin Yang; Xue-pei Fan; Chen-chen Bi; Lan-mei Ke; Ye Yang; Da Zhang; Shu Wang (Applied Geophysics, 2026)

Study on the effect of heating and cooling paths on the macro- and micro-properties of red sandstone based on low-field NMR - Shuang Dang; Lin Ning; Jing Bi; Yu Zhao; Yuhang Zhao; Chaolin Wang; Zhongqian Chen (Bulletin of Engineering Geology and the Environment, 2026)

Pasteurella multocida toxin induces apoptosis of respiratory epithelial cells by activating the PERK–NF-κB-DR5 signaling axis - Fei Wang; Yuhao Lei; Menghan Chen; Haixin Bi; Yayuan Luo; Fangfang Bai; Lin Hua; Huanchun Chen; Qigai He; Bin Wu; Zhong Peng (Veterinary Microbiology, 2026)

Flocculation dynamics of suspended particulate matter under various tidal conditions - Mingze Lin; Xiaoteng Shen; Changjian Xu; Michael Fettweis; Byung Joon Lee; Qilong Bi; Peter Robins; Xiaorong Li; Jerome P.-Y. Maa; Gang Wang (Journal of Hydrology, 2026)

Involvements of dicyclohexylcarbodiimide and adenosine diphosphate-mediated respiration and organic acid metabolisms in pulp acidification of Phomopsis longanae Chi-infected longan fruit - Weiting Bi; Yueying Sang; Wen Lin; Ruiling Zhuo; Mengshi Lin; Yihui Chen; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Food Chemistry, 2026)

Structural vibration analysis and safety assessment of centrifuges under hypergravity environments - Chengpeng Hong; Guanwen Liang; Li Bi; Haoran Fu; Zizhuang Yan; Kuigen Lin; Yunmin Chen (Engineering Structures, 2026)

Achieving 17.65% efficiency in organic solar cells by neutral linker engineering in dimerized small-molecule acceptors - Jianan Niu; Xue Zhou; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Cheng Sun; Tan Wang; Mingliang Sun; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2026)

Effects of Water-Fertilizer-Tillage Management on NH₃ Volatilization and Nitrogen Deposition in a Typical South China Agricultural System - Xiaoming He; Lingling Bi; Tianyi Chen; Siqi Yang; Shujuan Zhang; Siyi Yang; Chaohui Chen; Xin Wu; Xingjian Yang; Xueming Lin; Yongtao Li; Zhen Zhang (Water, Air, & Soil Pollution, 2026)

Macro-mesoscopic deterioration characteristics of MICP-improved strongly weathered phyllite under wetting-drying cycles - Yuhang Zhao; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Ning; Yang Li (Bulletin of Engineering Geology and the Environment, 2026)

Investigation of Microdamage and Seepage Evolution in Sandstone Under Coupled Thermomechanical Loading and Cooling Shocks via NMR - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Zhang; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2026)

Effects of alkaline pretreatment on side-stream enhanced biological phosphorus removal and recovery process - Ruoyu Wu; Dongqi Wang; Yufan Wu; Lu Qin; Xiaonian Feng; Yi Xiao; Yanzhe Gong; Guangxiang Duan; Jiayu Bi; Zhiqiang Xu; Yuan Guo; Jiake Li; et al. (Journal of Water Process Engineering, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Molecular characteristics of water-soluble organic aerosols under pollution conditions in a coal resource-based city revealed by FT-ICR MS: a significant role of sulfur-containing compounds - Chao Zhang; Ziyong Guo; Qingyu Hu; Lin Qi; Yang Chen; Yufeng Zhao; Nan Pei; Wei Sun; Xiaodong Hu; Yuxiang Yang; Fengxian Liu; Ling Mu; et al. (Fuel, 2026)

Strategy for doubling the yield of phenolics in hydrothermal liquefaction of Arundo donax: mechanistic study on weak alkaline catalyst suppressing hydrochar formation and enriching phenolics in aqueous and biocrude phases - Lei-ming Bi; De-lin Fu; Xian-shuai Fu; Li-hui Zhang; Feng Duan (Biomass and Bioenergy, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

Synergy or conflict? Assessing the combined emission reduction effects of environmental taxation and carbon trading in China's power sector - Song Chai; Jin Yang; Xintian Bi; Lin Tang; Maiyue Zhang; Jie Zhu (Utilities Policy, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Investigating chloride sources for lithium extraction from spent lithium iron phosphate batteries using TBP: Focusing on inherent iron utilization - Xitong Bi; Xiaojiao Li; Tiantian Zhao; Pengfei Ma; Mingzhang Lin; Yinxi Zhou (Hydrometallurgy, 2026)

Coal tar phenolic DES back-extraction study based on Hansen parameters: A combined experimental and computational approach - Dezhi Cao; Dingkai Hu; Wenna Wang; Xinyue Lin; Xinpeng Bi; Jun Tang; Qiang Wang (Fuel, 2026)

A novel antimicrobial peptide FxCy2 against Helicobacter pylori: Isolation and purification from Lactobacillus paracasei FX-6 - Bo Bi; Meng Kang; Qianru Lin; Qun Wang; Xiaoqing Li; Zhuming Ye; Chi-Tang Ho; Yong Cao (Food Research International, 2026)

Isolation and Nitrogen Removal Characteristics of a Novel Salt-Tolerant Aerobic Denitrifier Marinobacter sp. Strain B108 - Xinqiang Liu; Wenxin Wang; Haisong Bi; Shilin Lin; Zheng Wang; Chengduo Qian; Jiushu Lin; Junyuan Ji (Journal of Ocean University of China, 2026)

Human-induced changes in fluvial regimes for organic carbon supply and burial off the Yellow River Estuary - Li Jiang; Limin Hu; Naishuang Bi; Jinya Xu; Jun Ye; Lin Liu; Fudong Lin; Weini Chong; Jiazong Du; Xiao Wu; Houjie Wang (Water Research, 2026)

Recovery mechanisms of deteriorated nitrogen removal in aerobic granular sludge with/without salinity stress: Enhanced nitrification and transformed denitrification pathways - Zihan Sheng; Jie Xu; Shichang Liu; Yuan Gao; Xuejun Bi; Shujuan Huang; Dong Chen; Lin Li (Environmental Research, 2026)

Numerical study on natural ventilation of equipment rooms in underground subway stations - Jiaoyi Wei; Yuanlong Zhou; Congyun Lin; Haiquan Bi; Kai Liu (Energy and Buildings, 2026)

Neurodevelopmental toxicity induced by iron oxide nanoparticles: Insights from chick and zebrafish embryonic models - Bi-Xia Huang; Tao Zhang; Qing-Bin Dong; Peng-Xing Lin; Yi Zhou; Xin-Shuo Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Modulating excited states of multiple resonance emitter via through-space conjugation toward pure-green electroluminescence - Xiaoxian Song; Junxuan Lin; Zhiqiang Li; Zhiping Yan; Xuming Zhuang; Hai Bi; Yue Wang (Chemical Engineering Journal, 2026)

Adiponectin Signaling Ameliorates Cognitive Dysfunction in Type 2 Diabetic Mice by Activating the Hippocampal AdipoR2-PPARα/CREB Pathway - Hongyan Gong; Yanli Liu; Liu Xia; Bochao Niu; Jian Kong; Bin Wang; Xu Lin; Lin Lin; Yanlin Bi (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Thickened active layer contribute less to vegetation growth over the Tibetan Plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Wuxia Bi; Lin Zhu; Zhaoyu Dong; Yuhang Zhang; Jianyun Zhang; Hao Wang (Journal of Hydrology, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Spotted knifejaw (Oplegnathus punctatus) TARBP2 negatively regulates type I IFN responses to promote RGNNV replication - Yijie Lin; Weifu Mo; Xinyu Liao; Minyao Bi; Siting Wu; Qiwei Qin; Jingguang Wei (Fish & Shellfish Immunology, 2025)

A cellulose-based near-infrared fluorescent probe for ratiometric imaging and visual monitoring of ClO− in water via smartphone - Wei Bi; Chuanli Ren; Yuxin Xiao; Feng Wang; Qingmao Long; Yanfei Lin; Xinjie Yang; Li Liu; Lianpeng Zhang; Guanben Du (Environmental Research, 2025)

Microdomain tuning of sulfhydryl-COF in polymer electrolytes enables highly stable solid-state lithium batteries - Linnan Bi; Jiajun Li; Wenxin Peng; Ying Lin; Xiongbang Wei; Sizhe Wang; Jiaxuan Liao (Chemical Engineering Journal, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Modeling two-dimensional soil water–heat–salt transport and cotton growth under strip-film mulched drip irrigation - Dong Lin; Xi Huang; Wenping Bi; Yin Zhao; Xiaomin Mao (Agricultural Systems, 2025)

Intercellular crosstalk within human preimplantation lineages regulates trophectoderm specification - Zhifen Tu; Yan Bi; Tan Lin; Tao Wu; Hong Wang; Jingyu Li; Guoning Huang; Shaorong Gao; Yixuan Wang (Science Bulletin, 2025)

An amino functionalized iron based biochar for enhanced remediation for lead and lanthanum co-contaminated soil: Stress alleviation and stabilization mechanism - Fuxuan Bi; Zhao Jiang; Shuai Shi; Jia Qi; Mengning Wang; Qiutong Lin; Lei Wang; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2025)

An overlooked health risk of PM2.5: Elevated respiratory viral susceptibility revealed by assessing inflammatory and antiviral responses to chemical constituents - Shuyi Peng; Juying Lin; Wei Sun; Yaohao Hu; Baichuan Gou; Guohua Zhang; Wei Song; Bin Jiang; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Atmospheric Environment, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Coal Seam Geological Implicit Modeling with Fault Networks and Kinematic Parameters - Zhaohao Wu; Deyun Zhong; Liguan Wang; Lin Bi (Mathematical Geosciences, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Flexible supercapacitors with biomass-derived nitrogen-functionalized few-layer carbon for wireless energy harvesting and management - Dayong Ren; Peihao Yang; Jiaqi Wang; Zhengxiang Song; Pengyue Wu; Zhanqiang Liu; Tianquan Lin; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Study on combustion characteristics and mechanism of coal gangue under isothermal conditions - Haobo Bi; Jun Chen; Chunlong Jiang; Qizhao Lin (Fuel, 2025)

Impacts of prolonged power interruption on methane production in MEC-AD systems: Processes and mechanisms - Ling Wang; Chenxin Zhu; Haichao Luo; Xiaoqiu Lin; Yue Ma; Xuejun Bi; Wenzong Liu; Heliang Pang (Chemical Engineering Journal, 2025)

Active and stable platinum-indium single atom alloy catalysts for propane dehydrogenation - Jilei Lin; Meiqing Shen; Chunjuan Zhang; Sifeng Bi; Gurong Shen; Feng Gao; Wei Li (Chemical Engineering Journal, 2025)

Influence of roots on soil preferential paths for infiltration in typical vegetation of the Loess Plateau - Ning Guan; Huaxing Bi; Yilin Song; Shanhong Lu; Dandan Lin; Jindan Han (CATENA, 2025)

Organic matter accelerated microbial iron reduction and available phosphorus release in reflooded paddy soils - Xipeng Liu; Yuchen Shu; Kejie Li; Haotian Wang; Qingfang Bi; Haibo Wang; Chengliang Sun; Xianyong Lin (Soil Ecology Letters, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Improved Stability of Aerobic Granular Sludge Under Low Hydraulic Shear Force by Adding Magnetic Modified Low Expansion Vermiculite as Nucleating Agent - Wenjuan Xiang; Yuan Gao; Jie Xu; Xuejun Bi; Lin Li; Shu Chen (Water, Air, & Soil Pollution, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

Potential viral influence on sulfur metabolism in acid sulfate soils - Li Bi; Shuai Du; Rob Fitzpatrick; Qing-Lin Chen; Thi Bao-Anh Nguyen; Zi-Yang He; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Designing advanced high-entropy alloy sensors for sensitive low-temperature acetone detection - Boyan Fu; Leyao Bi; Jiahui Lin; Junsheng Wen; Jiaxing Fu; Binglin Zou; Chunjie Wang; Yue Wang (Journal of Environmental Chemical Engineering, 2025)

Machine learning algorithm facilitates fast derivation of light-scattering properties of sea salt aerosol - Quan Lin; Bingqi Yi; Lei Bi; Zhiyong Yang (Journal of Aerosol Science, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Isotopic Analysis for Tracing Vertical Growth Trajectories of Hailstones - Xiangyu Lin; Haifan Zhang; Xiaofei Li; Qinghong Zhang; Andrew Heymsfield; Kai Bi; Chan-Pang Ng; Chong Wu; Dianli Gong (Advances in Atmospheric Sciences, 2025)

ZCCHC3 inhibits PEDV proliferation by degrading nuclear coat proteins via the proteasome pathway - Zuyao Zhang; Shuangyang Wang; Huihui Sun; Jie Li; Jun Wang; Yangfan Li; Haichen Lin; Xuan Wang; Ruimin Bi; Zongyi Bo; Haixiao Shen; Liang Li; et al. (Veterinary Microbiology, 2025)

Molecular dynamics simulation revealing the interactions between toxic aldehydes and starch: A case study of malondialdehyde, 4-hydroxy-2-hexenal, and 4-hydroxy-2-nonenal in starch-based food during frying - Feng Wang; Xianhong Bi; Yun Cui; Kewei Lin; Charles Brennan; Soottawat Benjakul; Gengsheng Xiao; Lukai Ma (Food Chemistry, 2025)

A state-of-the-art review of bridges subjected to earthquake fault ruptures - Yuanzheng Lin; Yejing Chen; Zhouhong Zong; Kaiming Bi (Engineering Structures, 2025)

Revealing the Effect of Pore Size Distribution Characteristics on Macroscopic Properties of Red Sandstone Under Instantaneous High Temperature Through the Lens of Shannon Entropy Theory - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Yang Li; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2025)

Chemical profiles and mechanisms insights into Liuwei Dihuang-based formulas in diabetic nephropathy treatment: An integrated transcriptomics with in vitro experiments - Yanxia Liu; Anlei Yuan; Zewen Wang; Shijie Bi; Zhenzhen Xu; Chaoqun Liu; Bin Yu; Jiaye Tian; Liansheng Qiao; Zhaozhou Lin; Jun Jia; Yanling Zhang (Food Bioscience, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Mutation in FvPAL2 leads to light red strawberry fruits and yellow-green petioles - Chong Wang; Anqi Lin; Yankong Zhou; Zheng Liu; Peng Bai; Yuxuan Zhu; Junmiao Fan; Xiaoyi Bi; Huiyun Kuang; Hongli Lian; Pengbo Xu (Plant Science, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

A comparative study on the formation of nitrogen-containing organic compounds in cloud droplets and aerosol particles - Guohua Zhang; Tao Wang; Qinhao Lin; Kun Liu; Wei Sun; Duohong Chen; Lei Li; Xinming Wang; Xinhui Bi (Journal of Environmental Sciences, 2025)

Dimerized small-molecule acceptors with electron withdrawing linker for efficient organic solar cells - Jianan Niu; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Shuguang Wen; Cheng Sun; Mingliang Sun; Xichang Bao (Chemical Engineering Journal, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Synthesis and antibacterial activity of environmentally friendly sulfonium compounds - Jing Li; Wenyang Chen; Xinrui Bi; Yue Lin; Chengcai Liu; Yan Sun; Guinan Shen (Medicinal Chemistry Research, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Charged defect management for high-efficiency planar solar cells: Reducing charge recombination and open-circuit voltage loss by employing donor-acceptor molecules to regulate perovskite electronic properties - Miao Yu; Lin Fan; Lixue Wang; Chuanlong Bi; Yuan Gao; Jiadong Liu; Fengyou Wang; Xin Li; Qiong Wu; Xiaoyan Liu; Huilian Liu; Lili Yang (Chemical Engineering Journal, 2025)

Scratched surface: Quantifying the impact and evaluating underwater cleaning efficacy on fouling release coatings - Shujie Lin; Huichao Bi; Claus Erik Weinell; Kim Dam-Johansen (Ocean Engineering, 2025)

Land rights, resource allocation and urban settlement choices of migrant workers in Yunnan, Western China - Youqing Fan; Mengtao Gao; Lanlan Bi; Chyi Lin Lee; Guangbo Yin (Land Use Policy, 2025)

One-step microwave method synthesis of N, S-codoped carbon with the frustrated Lewis pairs for Cr (VI) removal - Liwen Wang; Yixin Sha; Changjun Bi; Daoqing Lin; Yuxue Liu; Lichun Dai; Xiaozhi Wang; Hui Lin; Jawad Ahmad Jrar; Jianhua Hou (Journal of Water Process Engineering, 2025)

Molecular characteristics of organic matters in PM2.5 associated with upregulation of respiratory virus infection in vitro - Juying Lin; Wei Sun; Shuyi Peng; Yaohao Hu; Guohua Zhang; Wei Song; Bin Jiang; Yuhong Liao; Chenglei Pei; Jinpu Zhang; Jianwei Dai; Xinming Wang; et al. (Journal of Hazardous Materials, 2025)

Enhanced rock weathering boosts ecosystem multifunctionality via improving microbial networks complexity in a tropical forest plantation - Xing Wang; Guochen Li; Arshad Ali; Camelia Algora; Manuel Delgado-Baquerizo; Daniel S. Goll; Sara Vicca; Tongtong Xu; Boyuan Bi; Qiong Chen; Luxiang Lin; Yunting Fang; et al. (Journal of Environmental Management, 2025)

Influence of different oxides on the combustion process of nano aluminum - Chunlong Jiang; Haobo Bi; Qizhao Lin; Zhanshi Ni (Fuel, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Exploring the mechanism of ursolic acid in preventing liver fibrosis and improving intestinal microbiota based on NOX2/NLRP3 inflammasome signaling pathway - Qi Liu; Lin-Xiang Liu; Bi-Min Li; Wang Zhang; Yue Zhang; Peng Chen; Chen-Kai Huang; Yuan Nie; Xuan Zhu (Chemico-Biological Interactions, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

A segmented grid model for vertical adjustment of precipitable water vapor in China - Maijin Lin; Shaofeng Xie; Liangke Huang; Lilong Liu; Yicai Wang; Haohang Bi; Qingwen Huang (Advances in Space Research, 2025)

Establishment of Biopredictive Dissolution and Bioequivalence Safe Space Using the Physiologically Based Biopharmaceutics Modeling for Tacrolimus Extended-Release Capsules - Fulin Bi; Tong Yuan; Baohong Zhang; Jixia Li; Yan Lin; Jin Yang (AAPS PharmSciTech, 2024)

Response of aerobic granular sludge to salinity fluctuations in formation, stability and microbial community structures - Jie Xu; Shichang Liu; Jiazhong Zhou; Lin Li; Xuejun Bi; Wenjie Han; Di Wu (Science of The Total Environment, 2024)

C:N stoichiometry and the fate of organic carbon in ecosystems of the northwest Pacific Ocean - Chuanli Zhang; Yaoyao Wang; Rong Bi; Ulrich Sommer; Guodong Song; Zhaohui Chen; Feng Lin; Jing Zhang; Meixun Zhao (Progress in Oceanography, 2024)

A novel improved actuator line method for tandem-arranged wind turbines wake analysis and its application - Ning Fan; Xianxu Yuan; Wenyang Duan; Lin Bi (Ocean Engineering, 2024)

Settling and rising velocities of microplastics: Laboratory experiments and lattice Boltzmann modeling - Xiaoteng Shen; Mingze Lin; Haoyu Chong; Jinfeng Zhang; Xiaorong Li; Peter Robins; Qilong Bi; Yuliang Zhu; Ying Zhang; Qiqing Chen (Environmental Pollution, 2024)

A new method to estimate the soil freezing characteristic curve - Jun Bi; Chaozheng Shen; Guoxu Wang; Zhijian Wu; Sheng Yang; Jianguo Lu; Gaochao Lin (Cold Regions Science and Technology, 2024)

In-situ synthesis of 2D nanozymes-coated cellulose nanofibers on paper-based chips for portable detection of biothiols - Chao Di; Yiwei Zhang; Lian Xue; Wenyi Zeng; Tengteng Wang; Yiwei Lin; Peng Chen; Xiaojun Feng; Wei Du; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Structure and transport properties of FeS at planetary core conditions - E. Edmund; T. Bi; Z.M. Geballe; K. Brugman; J.-F. Lin; S. Chariton; V.B. Prakapenka; J. Minár; R.E. Cohen; A.F. Goncharov (Earth and Planetary Science Letters, 2024)

Drugs targeting TGF-β/Notch interaction attenuate hypertrophic scar formation by optic atrophy 1-mediated mitochondrial fusion - Da Huo; Xin-yu Bi; Jun-ling Zeng; Da-mao Dai; Xiang-lin Dong (Molecular and Cellular Biochemistry, 2024)

Insights into the individual and combined effects of Cu(Ⅱ) and Ni(Ⅱ) on anammox: Nitrogen removal performance, enzyme activity and microbial community - Minghao Mu; Dengzhi Li; Shilin Lin; Haisong Bi; Xinqiang Liu; Zheng Wang; Chengduo Qian; Junyuan Ji (Chemosphere, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Bio-refinery of organic pollutants for wastewater reclamation - Haifeng Zhang; Yi Zhang; Sudan Lin; Xuejun Bi; Shujuan Huang; Bo Jiang; Dong-Hoon Kim; How Yong Ng; Xueqing Shi (Chemical Engineering Journal, 2024)

A dual-action Rhein-peptide hydrogel synergistically inhibits inflammation and matrix degradation for therapeutic mitigation of abdominal aortic aneurysm - Mingliang Wang; Yaling Li; Yizhou Bai; Zien Lin; Shenghui Bi; Yunxiang Long; Yanbin Cai; Xiaowu Wang (Chemical Engineering Journal, 2024)

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

DNA demethylase Tet2 promotes the terminal maturation of natural killer cells - Yuqing Lin; Biyun Yang; Hailin Liu; Guanghe Ran; Liang Song; Meng Meng; Xiaofeng Yin; Qinghua Bi; Dongmei Yan; Youcai Deng; Yonghui Lu (Immunologic Research, 2024)

Optical Modeling of Sea Salt Aerosols Using in situ Measured Size Distributions and the Impact of Larger Size Particles - Wushao Lin; Lei Bi (Advances in Atmospheric Sciences, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

Distribution of soil tardigrades as revealed by molecular identification across a large-scale area of Australia - Zi-Yang He; Hang-Wei Hu; Bao-Anh Thi Nguyen; Qing-Lin Chen; Anthony Weatherley; Michael Nash; Li Bi; Keren Wu; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Correlation between Antibiotics-Resistance, Virulence Genes and Genotypes among Klebsiella pneumoniae Clinical Strains Isolated in Guangzhou, China - Yi-Lin Hu; Shui-Lian Bi; Zang-Yun Zhang; Nian-Qing Kong (Current Microbiology, 2024)

Sedimentary record of water-sediment regulation and channel shifts in the Yellow River (Huanghe) Delta - Shuqing Qiao; Xuefa Shi; Jianbu Wang; Lin Zhou; Yonggui Yu; Naishuang Bi; Limin Hu; Gang Yang; Zhengquan Yao (Marine Geology, 2024)

Glycosylation of a ferritin nanocage with dextran as a novel emulsifier for the construction of dual-compartmental pickering emulsions to co-encapsulate hydrophobic bioactive compounds - Guo Yuanhao; Wang Yaxin; Dong Pengfei; Wang Shengnan; Lin Kai; Hou Jiangyan; Cui Fangming; Bi Shuyu; Cao Jinling; Cheng Yanfen; Cheng Feier; Yun Shaojun; et al. (Journal of Food Engineering, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

Vegetation restoration is affecting the characteristics and patterns of infiltration in the Loess Plateau - Ning Guan; Huaxing Bi; Yilin Song; Shanhong Lu; Dandan Lin; Jindan Han (CATENA, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Diagnosis of the accuracy of land cover classification using bootstrap resampling - Tong Yang; Binghong Han; Xiaofei He; Ziqi Ye; Yongli Tang; Jiexin Lin; Xia Cui; Jian Bi (International Journal of Remote Sensing, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Discovery of the tigecycline resistance gene cluster tmexCD3-toprJ1 in Pasteurella multocida strains isolated from pigs in China - Congcong Shi; Zhanwei Zhu; Yuyao Shang; Wenbo Song; Jie Yang; Haixin Bi; Zihao Wang; Rui Xie; Mengfei Zhao; Lin Hua; Huanchun Chen; Bin Wu; et al. (Veterinary Microbiology, 2024)

N6-methyladenosine analysis unveils key mechanisms underlying long-term salt stress tolerance in switchgrass (Panicum virgatum) - Huayue Liu; Mengzhuo Lin; Hui Wang; Xue Li; Die Zhou; Xiaojing Bi; Yunwei Zhang (Plant Science, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Advances in Atmospheric Radiation: Theories, Models, and Their Applications. Part I: Atmospheric Gas Absorption and Particle Scattering - Hua Zhang; Liting Liu; Lei Bi; Wushao Lin; Chao Liu; Bingqi Yi; Lei Liu; Qi Chen; Xiaodong Wei; Husi Letu; Zhengqiang Li; Wenwen Li (Journal of Meteorological Research, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Nonlinear effects of surface soil moisture changes on vegetation greenness over the Tibetan plateau - Wenwen Li; Denghua Yan; Baisha Weng; Yuequn Lai; Lin Zhu; Tianling Qin; Zhaoyu Dong; Wuxia Bi (Remote Sensing of Environment, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Roles and sources of B vitamins in the marine ecosystem - Lin Wang; Hancheng Zhao; Ran Bi; Xiaohan Chen; Zhendong Lyu; Wenhua Liu (Reviews in Fish Biology and Fisheries, 2024)

Performance and mechanism of sequential UV-NaClO disinfection: Inactivation and reactivation of antibiotic-resistant bacteria, disinfection byproduct formation and microbial community variation - Lihua Cheng; Xiaohan Wei; Aili Gao; Lin Zhou; Xueqing Shi; Xiaolin Zhou; Xuejun Bi; Tang Yang; Shujuan Huang (Journal of Water Process Engineering, 2024)

Effect of lignin on coal slime combustion characteristics and carbon dioxide emission - Zhanshi Ni; Haobo Bi; Hao Shi; Xiang Liu; Junjian Tian; Yurou Yao; Liqun He; Kesheng Meng; Qizhao Lin (Journal of Cleaner Production, 2024)

Unveiling the nitrogen and phosphorus removal potential: Comparative analysis of three coastal wetland plant species in lab-scale constructed wetlands - Xiaoqing Gao; Yuxin Bi; Lin Su; Ying Lei; Lv Gong; Xinhan Dong; Xiuzhen Li; Zhongzheng Yan (Journal of Environmental Management, 2024)

Directional guiding of mass and charge transfer via vertically aligned graphite nanosheets for high-rate and ultralong lifespan Dual-ion batteries - Lin Shang; Bi-Yun Shi; Xianchun Liu; Tian-Tian Zhang; Hanlin Liu; Yongping Zheng; Wei-Dong Dou; Qingguang Pan; Yongbing Tang (Chemical Engineering Journal, 2024)

TGF-β1/Smad3 Signaling Is Required to Alleviate Fluoride-Induced Enamel Hypomineralization - Ruonan Bi; Yiqun Sun; Lili Xiang; Zhenzhen Xu; Xiaoyuan Ye; Yanying Tian; Yao Lin; Chunyan Yang; Yuguang Gao (Biological Trace Element Research, 2024)

Effect of human chorionic gonadotrophin (HCG) and luteinizing hormone releasing hormone A3 (LHRH-A3) on reproduction and development of brood pouch in Hippocampus erectus - Xuange Liu; Gongpei Wang; Jiahui Chen; Sheng Bi; Chenlei Huang; Han Lai; Huadong Yi; Haiyang Li; Qiuxian Chen; Li Lin; Zhilun Zhang; Xuchong Wei; et al. (Aquaculture, 2024)

Unveiling the impact of flooding and salinity on iron oxides-mediated binding of organic carbon in the rhizosphere of Scirpus mariqueter - Yuxin Bi; Xiaoqing Gao; Lin Su; Ying Lei; Tianyou Li; Xinhan Dong; Xiuzhen Li; Zhongzheng Yan (Science of The Total Environment, 2024)

Can public opinion persuade the government to strengthen the use of environmental regulation policy tools? Evidence from policy texts - Song Chai; Mengxian Wei; Lin Tang; Xintian Bi; Yawen Yu; Jin Yang; Zhu Jie (Journal of Cleaner Production, 2024)

Anthropogenic influence has significantly affected snowfall changes in Eurasia - Wenqing Lin; Huopo Chen; Weiqi Wang; Dawei Zhang; Fan Wang; Wuxia Bi (Atmospheric Research, 2024)

Lineaperpetua gen. nov.: a new diatom genus in the Thalassiosirales supported by morphology and molecular data - Pan Yu; Lin Yang; Qingmin You; John Patrick Kociolek; Kangyu Wang; Yonghong Bi; Quanxi Wang (Journal of Oceanology and Limnology, 2024)

Stress drop variations of the 2019 ML 6.0 Changning earthquake and its aftershock sequence in the southern Sichuan Basin, China - Lin Shen; Lian-Feng Zhao; Xiao-Bi Xie; Xi He; Wei-Min Wang; Zhen-Xing Yao (Tectonophysics, 2023)

Ligand-engineered Ni-based metal–organic frameworks for electrochemical oxygen evolution reaction - Zhenzhen Xu; Yuan Tao; Zhaodi Sun; Peiyan Bi; Xing Zhong; Jiajun Liao; Dacheng Hao; Licheng Yang; Lin Xu; Mingbiao Luo; Kecheng Pan; Zhi Gao (Chemical Engineering Journal, 2023)

The dual role of potassium ferrate in promoting primary sludge hydrolysis and acidogenesis in anaerobic fermentation - Ling Wang; Chang Liu; Xing Fan; Thangavel Sangeetha; Kailing Pan; Xuejun Bi; Wenzong Liu; Xiaoqiu Lin; Xiaodong Wang; Aijie Wang; Heliang Pang (Chemical Engineering Journal, 2023)

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

Rapid Genotyping of Campylobacter coli Strains from Poultry Meat by PFGE, Sau-PCR, and fla-DGGE - Ge-Feng Yao; Yi-Lin Hu; Nian-Qing Kong; Jin-Hong Liu; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Current Microbiology, 2023)

Long non-coding RNA LOC103222771 promotes infection of porcine reproductive and respiratory syndrome virus in Marc-145 cells by downregulating Claudin-4 - Xinxian Wang; Junlong Bi; Chao Yang; Yongneng Li; Ying Yang; Junwen Deng; Lei Wang; Xiaolin Gao; Yingbo Lin; Jianping Liu; Gefen Yin (Veterinary Microbiology, 2023)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

Health risk assessment of trace metal(loid)s in agricultural soil using an integrated model combining soil-related and plants-accumulation exposures: A case study on Hainan Island, South China - Bi-gui Lin; Pan Pan; Chao-xian Wei; Xi-chao Chen; Zong-yao Zhang; Qing-fang Fan; Fang Liu; Bei-bei Liu; Lin Wu (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chalcogen-modified copper-nitrogen co-doped carbon as a stable and efficient antimicrobial cathode catalyst for microbial fuel cells - Bi-Lin Lai; Hai-Xia Liao; Shu-Qi Zhou; Hui-Xu Wei; Ai-Yi Li; Nan Li; Zhao-Qing Liu (Journal of Environmental Chemical Engineering, 2023)

Highly efficient production of monocyclic aromatics from catalytic co-pyrolysis of biomass and plastic with nitrogen-doped activated carbon catalyst - Xiaona Lin; Xiaoyun Chen; Peng Fu; Binbin Tang; Dongmei Bi (Chemical Engineering Journal, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Development of microfluidic chip flowmeter-based constant pressure system for analysing the hydrogen adsorption performance of non-evaporable getters - Wenyu Lin; Wei Wei; Jun Wu; Qing Cao; Hailin Bi; Jun Zhang; Zhengwei Mei; Jian Jin; Xudi Wang (Analytica Chimica Acta, 2023)

Dual-targeting lanthanide-ICG-MOF nanoplatform for cancer Theranostics: NIR II luminescence imaging guided sentinel lymph nodes surgical navigation - Bi Lin; Ruiyi Dai; Zhenghao Liu; Wenjing Li; Jingwen Bai; Guojun Zhang; Ruichan Lv (Journal of Photochemistry and Photobiology B: Biology, 2023)

Physicochemical properties, structural characteristics and in vitro digestion of brown rice–pea protein isolate blend treated by microbial transglutaminase - Lin Zhao; Ming-Hsu Chen; Xuezhi Bi; Juan Du (Food Hydrocolloids, 2023)

Effective conversion of corn stalk into ethyl levulinate and crude lignin catalyzed by ionic liquids - Xiaoqi Lin; Kaisen Jiang; Xuebin Liu; Hongyan Bi; Tianya Li; Dezhi Han; Qinqin Zhang (Biomass and Bioenergy, 2023)

Food aflatoxin exposure assessment in Sichuan Province, China - Bi Zhao; Yi Xu; Yang Song; Yu Zhang; Li Lin (Mycotoxin Research, 2023)

Legacy and novel perfluoroalkyl substances in major economic species of invertebrates in South China Sea: Health implication from consumption - Jieyi Diao; Zhenwei Chen; Chuanghong Su; Jianwen Wang; Zhixin Zheng; Qiongping Sun; Lin Wang; Ran Bi; Tieyu Wang (Marine Pollution Bulletin, 2023)

Study on combustion characteristics of nano-aluminum in different gas atmospheres and environment temperatures - Chunlong Jiang; Haobo Bi; Zhanshi Ni; Hao Sun; Hao Shi; Qizhao Lin (Fuel, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Mining of kokumi peptides in chicken broth with peptidomics - Yang Li; Jicai Bi; Zeyuan Lin; Zhen Yang; Yueyue Gao; Chunyuan Ping; Zhuo Chen (International Journal of Gastronomy and Food Science, 2023)

Extremely weak Lg attenuation reveals ancient continental relicts in the South China block - Lin Shen; Lian-Feng Zhao; Xiao-Bi Xie; Geng Yang; Zhen-Xing Yao (Earth and Planetary Science Letters, 2023)

Brevilin A inhibits RANKL-induced osteoclast differentiation and bone resorption - Jinfu Wei; Zihong Lin; Zeyu Dai; Zibin Zhou; Yonghao Bi; Ruiwu Zheng; Xianghua Hu; Zhaoxin Xu; Guixin Yuan; Weidong Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Molecular characteristics, sources and transformation of water-insoluble organic matter in cloud water - Wei Sun; Ziyong Guo; Xiaocong Peng; Juying Lin; Yuzhen Fu; Yuxiang Yang; Guohua Zhang; Bin Jiang; Yuhong Liao; Duohong Chen; Xinming Wang; Xinhui Bi (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Analysis of the Microscopic Evolution of Rock Damage Based on Real-Time Nuclear Magnetic Resonance - Jing Bi; Lin Ning; Yu Zhao; Zhijun Wu; Chaolin Wang (Rock Mechanics and Rock Engineering, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Studies on the interaction of five triazole fungicides with human renal transporters in cells - Jing Nie; Jiabei Zhou; Yi Shen; Ruimiao Lin; Haihong Hu; Kui Zeng; Huichang Bi; Min Huang; Lushan Yu; Su Zeng; Jing Miao (Toxicology in Vitro, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China - Ziqing Li; Jianqing Zhang; Qian Meng; Lin Yang; Mingyang Qiu; Yun Li; Shuai Yao; Wenlong Wei; Changliang Yao; Qirui Bi; Jiayuan Li; De-an Guo (Food Research International, 2023)

Molecular engineering of Fe-MIL-53 electrocatalyst for effective oxygen evolution reaction - Yue Wang; Zhiyi Zhou; Yuzhi Lin; Yongzheng Zhang; Peiyan Bi; Qiqi Jing; Yidong Luo; Zhaodi Sun; Jiajun Liao; Zhi Gao (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Cytotoxic steroidal glycosides from the rhizomes of Paris polyphylla var. yunnanensis - Yang Liu; Mei-You Liu; Lin-Lin Bi; Yun-Yuan Tian; Peng-Cheng Qiu; Xiao-Ying Qian; Min-Chang Wang; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Phytochemistry, 2023)

Effect of dense phase carbon dioxide treatment on the flavor, texture, and quality changes in new-paocai - Yage Xing; Rumeng Yi; Tianyi Yue; Xiufang Bi; Lin Wu; Hongjie Pan; Xiaocui Liu; Zhenming Che (Food Research International, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

Adsorption and degradation of neonicotinoid insecticides in agricultural soils - Yang Li; Yadong Li; Guihong Bi; Timothy J. Ward; Lin Li (Environmental Science and Pollution Research, 2023)

The effect of cellulose on the combustion characteristics of coal slime: TG-FTIR, principal component analysis, and 2D-COS - Zhanshi Ni; Zhihui Song; Haobo Bi; Chunlong Jiang; Hao Sun; Zhicong Qiu; Liqun He; Qizhao Lin (Fuel, 2023)

Discovery of inhibitors against SARS-CoV-2 main protease using fragment-based drug design - Hai Ping Shao; Tian Hua Wang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Chemico-Biological Interactions, 2023)

Molecular characteristics and compositions affecting light absorption features of cloud water revealed by Fourier transform ion cyclotron resonance mass spectrometry - Ziyong Guo; Wei Sun; Xiaodong Hu; Juying Lin; Yuzhen Fu; Xiaocong Peng; Bin Jiang; Yuhong Liao; Guohua Zhang; Xinming Wang; Ping'an Peng; Xinhui Bi (Atmospheric Environment, 2023)

A two-sorbent system for fast uptake of arsenate from water: Batch and column studies - Zhengyang Wang; Xiangyu Bi; Xiaoqing He; Yunchao Xie; Jian Lin; Baolin Deng (Water Research, 2023)

ZIF-8-derived Cu, N co-doped carbon as a bifunctional cathode catalyst for enhanced performance of microbial fuel cell - Bi-Lin Lai; Hui-Xu Wei; Zi-Nuo Luo; Tong Zheng; Yi-Hui Lin; Zhao-Qing Liu; Nan Li (Science of The Total Environment, 2023)

Corrigendum to “Investigation of the co-pyrolysis of coal slime and coffee industry residue based on machine learning methods and TG-FTIR: Synergistic effect, kinetics and thermodynamic” [Fuel 305 (2021) 121527] - Zhanshi Ni; Haobo Bi; Chunlong Jiang; Chengxin Wang; Junjian Tian; Wenliang Zhou; Hao Sun; Qizhao Lin (Fuel, 2023)

Responses of phytoplankton and its satellite bacteria to exogenous ethanol - Rediat Abate; Buce Hanoch Hetharua; Vishal Patil; Daner Lin; Demeke Kifle; Junrong Liang; Changping Chen; Lin Sun; Shuh-Ji Kao; Yonghong Bi; Bangqin Huang; Yahui Gao (Journal of Oceanology and Limnology, 2023)

Systematic assessment of GPM IMERG V06 precipitation products with dense rain gauge observations over Zhejiang Province, China - Zaoying Bi; Shanlei Sun; Huayu Shen; Yi Liu; Yongjian Ren; Jinjian Li; Bin Lin (International Journal of Climatology, 2022)
This study systematically assessed the performance of the Integrated Multi‐satellitE Retrievals (IMERG) for Global Precipitation Measurement V06, including the near‐real‐time “Late Run” (IMERG‐L) and the post‐real‐time “Final Run” (IMERG‐F), over Zhejiang Province (ZJP), China. The evaluation was conducted at daily and hourly timescales for a full year and for each season, based on dense rain gauge observations and continuous and categorical validation statistics. For the full year and for each season, IMERG‐F outperformed IMERG‐L in representing the spatial pattern of multiyear mean precipitation. For regional mean of ZJP, IMERG‐F and IMERG‐L overestimated the daily/hourly precipitation for the full year by 6.51 and 4.98%, respectively. Among seasons, the regional mean relative biases for IMERG‐F were between 5.65 and 8.63%; however, for IMERG‐L, they exhibited notable variations with a maximum of 11.09% in fall and a minimum of 0 in spring. Bias composition suggested that the regional mean overestimations were largely due to false bias for the full year and for each season, except in winter, wherein it was due to hit bias. Spatially, the biases for the full year and for each season commonly arose from false and hit biases at daily timescale, and from false and miss biases at hourly timescale. Based on the remaining continuous metrics (i.e., root‐mean‐square‐error [RMSE], correlation coefficient [CC], and Kling–Gupta Efficiency [KGE]) and all categorical metrics, the IMERG daily/hourly performance was acceptable on regional and grid scales throughout the year and in all seasons. From a region‐average perspective, IMERG‐F outperformed IMERG‐L according to CC, RMSE, and KGE, but both products showed the same performance overall based on all categorical metrics; most grids also share these characteristics. This study provides a valuable reference for IMERG developers to improve product accuracy from the perspective of the final postprocessing step and for potential users in ZJP.

Rapid Determination in the Quality Control of Chinese Patent Medicine - Shao Hua Lu; Ming Cai Zhang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Journal of Pharmaceutical Innovation, 2022)

Synthesis and biological evaluation of new thiazolyl-urea derivatives as potential dual C-RAF/FLT3 inhibitors - Zhi-Hua Zhang; Bi-Fan Zeng; Zhe-Xue Song; Ying-Yu Yang; Kai-yun Zhang; Xue Du; Lin-lin Zhang; Dong Cai (Medicinal Chemistry Research, 2022)

Long‐term series variation in fishery biology of Dosidicus gigas off Peru: Response to climate variability from 2008 to 2020 - Ya Ting Dan; Bi Lin Liu; Xin Jun Chen; Wei Guo Qian (Fisheries Oceanography, 2022)
As a cephalopod with a short life cycle, the Dosidicus gigas (jumbo flying squid) is extremely sensitive to climate variability and marine environment changes in terms of individual growth and resource changes. Based on 7514 D. gigas samples collected off Peru from 2008 to 2020, the fishery biological characteristics such as size, sexual maturity, and size‐at‐maturity were analyzed to explore the impacts of climate variability on individual growth. The results showed that there were significant differences in the relationship between mantle length and body weight and in the composition of sexual maturity between male and female individuals in different years ( P D. gigas and slowed down their sexual maturity, producing D. gigas groups in medium and large sizes; El Niño events inhibited the individual growth of D. gigas and accelerated their sexual maturity, producing D. gigas groups in a smaller size. From 2008 to 2020, the mantle length of the small‐size group decreased by 46 mm, while that of the medium‐size group increased by 28 mm. Size‐at‐maturity of female D. gigas decreased by 201.2 mm and that of male D. gigas decreased by 143 mm. The study concluded that the changes in the marine environment caused by climate variability from 2008 to 2020 have had a significant impact on the population structure, growth, and development of the D. gigas off Peru.

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Response of reinforced mortar-less interlocking brick wall under seismic loading - Guanyu Xie; Xihong Zhang; Hong Hao; Kaiming Bi; Yuanzheng Lin (Bulletin of Earthquake Engineering, 2022)
Mortar-less construction with interlocking bricks has many advantages, such as improved construction efficiency and relatively low requirements on labour skills. Nevertheless, the seismic performance of interlocking brick structures is not well understood yet. In this paper, laboratory tests and numerical modelling are carried out to investigate the seismic behaviour of interlocking brick walls. Laboratory shaking table tests are performed on a scaled reinforced mortar-less interlocking brick wall. The response and damage modes under in-plane seismic loading are investigated. A detailed numerical model is then generated and validated with the laboratory testing data. Unlike the conventional masonry wall that diagonal shear damage governs the failure, the interlocking brick wall exhibits rocking responses, whose damage is mainly at the two bottom corners of the wall. Full-scale interlocking brick walls are then modelled and compared with conventional concrete masonry unit (CMU) walls bonded by mortar. Comparisons are made between the seismic resistances and damage modes of the two walls. The influences of ground motion intensities, vertical components of seismic excitations and different seismic time histories on the seismic behaviour of the interlocking brick wall are examined. It is found that the interlocking brick wall has a higher seismic resistance capacity than the conventional CMU wall. Inter-brick friction is the main energy dissipation mechanism in the interlocking brick wall. Because of the rocking response, vertical component of the ground motion significantly influences the damage of interlocking brick wall. The interlocking brick wall is insensitive to velocity pulses of ground motions due to its relatively high natural frequency.

Cross-generation trophic ecology of Dosidicus gigas in the eastern-central Pacific Ocean revealed from isotopic signatures in eye lenses - Guan Yu Hu; Zi Xin Wang; Bi Lin Liu; Meng Yao Huan; Xin Jun Chen (Fisheries Science, 2022)

One-Way Intestinal Perfusion of PVP/VA–Poloxamer 188–Curcuma longa L. Extract Solid Dispersion in Rats In Vivo and Its Effect on HSC–T6 Cell Proliferation - Jie Gao; Yi Shi; Yunfeng Han; Xi Tang; Ruohong Bi; Lin Pan; Xianrong Lai (AAPS PharmSciTech, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Optimal array layout of cylindrical baffles to reduce energy of rock avalanche - Yu-zhang Bi; Dong-po Wang; Xian-lei Fu; Yi-xiong Lin; Xin-po Sun; Zhe-yuan Jiang (Journal of Mountain Science, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Thermal Characteristics, Kinetics, and Volatility of Co-Combustion of Sewage Sludge and Rice Husk - Chengxin Wang; Haobo Bi; Qizhao Lin; Chunlong Jiang; Xuedan Jiang; Kesheng Meng (BioEnergy Research, 2021)

Local 3D scene fine detection analysis of circular landform on the southern edge of Dinosaur Valley - Gao Sha; Yuan Xiping; Gan Shu; Yang Milong; Hu Lin; Bi Rui (Arabian Journal of Geosciences, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Chinese construction industry energy efficiency analysis with undesirable carbon emissions and construction waste outputs - Xuedong Liang; Shifeng Lin; Xueyao Bi; Enfan Lu; Zhi Li (Environmental Science and Pollution Research, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

The TOR pathway participates in the regulation of growth development in juvenile spotted drum (Nibea diacanthus) under different dietary hydroxyproline supplementation - Hua Rong; Fan Lin; Yunlong Zhang; Baoliang Bi; Tengfei Dou; Xiangwei Wu; Jude Juventus Aweya; Xiaobo Wen (Fish Physiology and Biochemistry, 2020)

Numerical study of the seismic performance and damage mitigation of steel–concrete composite rigid-frame bridge subjected to across-fault ground motions - Yuanzheng Lin; Zhouhong Zong; Kaiming Bi; Hong Hao; Jin Lin; Yiyan Chen (Bulletin of Earthquake Engineering, 2020)

A minor QTL, SG3, encoding an R2R3-MYB protein, negatively controls grain length in rice - Qiuping Li; Li Lu; Haiyang Liu; Xufeng Bai; Xin Zhou; Bi Wu; Mengqi Yuan; Lin Yang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Wireless charging and shared autonomous battery electric vehicles (W+SABEV): synergies that accelerate sustainable mobility and greenhouse gas emission reduction - Zicheng Bi; Michael A. Reiner; Gregory A. Keoleian; Yan Zhou; Michael Wang; Zhenhong Lin (Mitigation and Adaptation Strategies for Global Change, 2020)

Fine mapping, candidate genes analysis, and characterization of a brown planthopper (Nilaparvata lugens Stål) resistance gene in the rice variety ARC5984 - Jiebin Lin; Xinyi Wang; Yang Li; Fanggui Bi; Ling Cheng; Fengkuang Huang; Rongbai Li; Yongfu Qiu (Euphytica, 2020)

Analysis of endophytic bacterial community diversity and metabolic correlation in Cinnamomum camphora - Guo-fang Zhang; Qiu-liang Huang; Xue-qin Bi; You-lin Liu; Zong-sheng Yuan (Archives of Microbiology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Sorption of ionic and neutral species of pharmaceuticals to loessial soil amended with biochars - Lin Wu; Erping Bi (Environmental Science and Pollution Research, 2019)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Optogenetic Long-Term Depression Induction in the PVT-CeL Circuitry Mediates Decreased Fear Memory - Ming Chen; Lin-lin Bi (Molecular Neurobiology, 2019)

Host genetic determinants of the gut microbiota of wild mice - Taichi A. Suzuki; Megan Phifer‐Rixey; Katya L. Mack; Michael J. Sheehan; Dana Lin; Ke Bi; Michael W. Nachman (Molecular Ecology, 2019)
Identifying a common set of genes that mediate host–microbial interactions across populations and species of mammals has broad relevance for human health and animal biology. However, the genetic basis of the gut microbial composition in natural populations remains largely unknown outside of humans. Here, we used wild house mouse populations as a model system to ask three major questions: (a) Does host genetic relatedness explain interindividual variation in gut microbial composition? (b) Do population differences in the microbiota persist in a common environment? (c) What are the host genes associated with microbial richness and the relative abundance of bacterial genera? We found that host genetic distance is a strong predictor of the gut microbial composition as characterized by 16S amplicon sequencing. Using a common garden approach, we then identified differences in microbial composition between populations that persisted in a shared laboratory environment. Finally, we used exome sequencing to associate host genetic variants with microbial diversity and relative abundance of microbial taxa in wild mice. We identified 20 genes that were associated with microbial diversity or abundance including a macrophage‐derived cytokine ( IL12a ) that contained three nonsynonymous mutations. Surprisingly, we found a significant overrepresentation of candidate genes that were previously associated with microbial measurements in humans. The homologous genes that overlapped between wild mice and humans included genes that have been associated with traits related to host immunity and obesity in humans. Gene–bacteria associations identified in both humans and wild mice suggest some commonality to the host genetic determinants of gut microbial composition across mammals.

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Klotho recovery by genistein via promoter histone acetylation and DNA demethylation mitigates renal fibrosis in mice - Yanning Li; Fang Chen; Ai Wei; Fangfang Bi; Xiaobo Zhu; Shasha Yin; Wenjun Lin; Wangsen Cao (Journal of Molecular Medicine, 2019)

Adsorption of Cd(II) from aqueous solution by Pennisetum sp. straw biochars derived from different modification methods - Guangcai Yin; Lulin Bi; Xiaowang Song; Haoyu Luo; Pengpeng Ji; Qintie Lin; Qianjun Liu; Guiyou Tang (Environmental Science and Pollution Research, 2019)

Cloning and Characterization of β-Fructosidase from Thermotoga neapolitana DSM4359 and Through the Degraded Glucoside - Yun-feng Bi; Lin-lin Xu; Ping Chen; Shan Jiang; Ming-hao Shen (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Roles of hydrophobic and hydrophilic fractions of dissolved organic matter in sorption of ketoprofen to biochars - Lin Wu; Ningwei Yang; Binghua Li; Erping Bi (Environmental Science and Pollution Research, 2018)

The tomato IQD gene SUN24 regulates seed germination through ABA signaling pathway - Lulu Bi; Lin Weng; Zhuyan Jiang; Han Xiao (Planta, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Differential Response of First-Order Lateral Root Elongation to Low Potassium Involves Nitric Oxide in Two Tobacco Cultivars - Wenjing Song; Ren Xue; Yao Song; Yang Bi; Zhihao Liang; Lin Meng; Caixia Dong; Chengdong Wang; Guangliang Liu; Jianxin Dong; Yali Zhang (Journal of Plant Growth Regulation, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Effect of Molecular Dissociation and Sorbent Carbonization on Bisolute Sorption of Pharmaceuticals by Biochars - Lin Wu; Binghua Li; Erping Bi (Water, Air, & Soil Pollution, 2017)

Periodic increments in the jumbo squid (Dosidicus gigas) beak: a potential tool for determining age and investigating regional difference in growth rates - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu; Wei Yu; Jin Tao Wang; Jing Yuan Lin (Hydrobiologia, 2017)

TIMAP repression by TGFβ and HDAC3-associated Smad signaling regulates macrophage M2 phenotypic phagocytosis - Jun Yang; Shasha Yin; Fangfang Bi; Lin Liu; Tian Qin; Hongwei Wang; Wangsen Cao (Journal of Molecular Medicine, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Copy Number Variations in Tilapia Genomes - Bi Jun Li; Hong Lian Li; Zining Meng; Yong Zhang; Haoran Lin; Gen Hua Yue; Jun Hong Xia (Marine Biotechnology, 2017)

Removal of polybrominated diphenyl ethers by biomass carbon-supported nanoscale zerovalent iron particles: influencing factors, kinetics, and mechanism - Rongbing Fu; Zhen Xu; Lin Peng; Dongsu Bi (Environmental Science and Pollution Research, 2016)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)

Dynamic patterns of circulating influenza virus from 2005 to 2012 in Shandong Province, China - Ti Liu; Zhong Li; Yi Lin; Shaoxia Song; Shengyang Zhang; Lin Sun; Yulu Wang; Aiqiang Xu; Zhenqiang Bi; Xianjun Wang (Archives of Virology, 2016)

Analyzing land use characteristics of rural settlements on the urban fringe of Liangjiang New Area, Chongqing, China - Yi Wang; Guo-hua Bi; Qing-yuan Yang; Zhao-lin Wang (Journal of Mountain Science, 2016)

The fractionation and geochemical characteristics of rare earth elements measured in ambient size-resolved PM in an integrated iron and steelmaking industry zone - Qili Dai; Liwei Li; Jiamei Yang; Baoshuang Liu; Xiaohui Bi; Jianhui Wu; YuFen Zhang; Lin Yao; Yinchang Feng (Environmental Science and Pollution Research, 2016)

The use of chlorogenic acid and its analogues as inhibitors: an investigation of the inhibition of sortase A of Staphylococcus aureus using molecular docking and dynamic simulation - Chongwei Bi; Lin Wang; Xiaodi Niu; Hongjun Cai; Xiaobo Zhong; Xuming Deng; Tiedong Wang; Dacheng Wang (Biotechnology Letters, 2016)

MeHg Suppressed Neuronal Potency of Hippocampal NSCs Contributing to the Puberal Spatial Memory Deficits - Jianying Tian; Yougen Luo; Weiwei Chen; Shengsen Yang; Hao Wang; Jing Cui; Zhiyan Lu; Yuanye Lin; Yongyi Bi (Biological Trace Element Research, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

Reconstructing cephalopod migration with statolith elemental signatures: a case study using Dosidicus gigas - Bi Lin Liu; Jie Cao; Samuel B. Truesdell; Yong Chen; Xin Jun Chen; Si Quan Tian (Fisheries Science, 2016)

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Two-dimensional inversion of spectral induced polarization data using MPI parallel algorithm in data space - Zhi-Yong Zhang; Han-Dong Tan; Kun-Peng Wang; Chang-Hong Lin; Bin Zhang; Mao-Bi Xie (Applied Geophysics, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Determination of squid age using upper beak rostrum sections: technique improvement and comparison with the statolith - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu (Marine Biology, 2015)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Spatial difference in elemental signatures within early ontogenetic statolith for identifying Jumbo flying squid natal origins - Bi Lin Liu; Yong Chen; Xin Jun Chen (Fisheries Oceanography, 2015)
Signatures of trace elements and isotopes in the parts of hard structures formed in the early ontogenetic stages can be used as potential natural tags of adult cephalopods to trace their origins. The Jumbo flying squid, Dosidicus gigas , is widely distributed in the eastern Pacific Ocean. Fourteen detected elemental signatures ( 7 Li, 23 Na, 24 Mg, 39 K, 43 Ca 55 Mn, 59 Co, 60 Ni, 63 Cu, 66 Zn, 88 Sr, 137 Ba, 208 Pb and 238 U) were determined in the nuclear zone (N), representing the embryonic stage, and the postnuclear zone ( PN ), representing the paralarval stage of statoliths for adult D. gigas collected off the Costa Rican, Peruvian and Chilean Exclusive Economic Zones ( EEZ s) using laser ablation inductively coupled plasma mass spectrometry ( LA ‐ ICP ‐ MS ). All measured signatures were significantly different between embryonic and paralarval statoliths, except for Sr, Ba and Pb. Over the three regions, a significant difference was found for Na and Ba within embryonic statoliths and Zn and Ba within paralarval statoliths. A high Ba/Ca ratio in statoliths obtained from Costa Rica was because of the prevalence of strong upwelling in the area. Elemental signatures, especially Ba/Ca, in early ontogenetic statoliths could be used as a proxy for distinguishing different geographical groups and identifying natal origins. However, elemental signatures in embryonic statoliths tended to be a better natural tag than those in paralarval statoliths indicating that paralarvae with the same origin had distinct dispersal pathways. Additionally, stepwise discriminant analysis ( SDA ) showed there were at least two migration‐based groups: ‘northern’ and ‘southern’ in the eastern Pacific Ocean. Overall, the derived results can improve our knowledge of the population structure, connectivity and life history of D. gigas .

Simultaneous determination of six constituents in Mahuang Fuzi Xixin by UPLC-PDA–MS/MS - Lin Zhang; Chengying Wang; Dezu Miao; Dan Yuan; Kaishun Bi; Jingyu Yang; Libin Zhan (Natural Product Research, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Association of soil arsenic and nickel exposure with cancer mortality rates, a town-scale ecological study in Suzhou, China - Kai Chen; Qi Lin Liao; Zong Wei Ma; Yang Jin; Ming Hua; Jun Bi; Lei Huang (Environmental Science and Pollution Research, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Mechanism-Based Pharmacokinetic Modeling to Evaluate Transporter-Enzyme Interplay in Drug Interactions and Pharmacogenetics of Glyburide - Manthena V. S. Varma; Renato J. Scialis; Jian Lin; Yi-An Bi; Charles J. Rotter; Theunis C. Goosen; Xin Yang (The AAPS Journal, 2014)

Probing the distribution and contamination levels of 10 trace metal/metalloids in soils near a Pb/Zn smelter in Middle China - Zhonggen Li; Xinbin Feng; Xiangyang Bi; Guanghui Li; Yan Lin; Guangyi Sun (Environmental Science and Pollution Research, 2014)

A knockdown mutation of YELLOW-GREEN LEAF2 blocks chlorophyll biosynthesis in rice - Hong Chen; Zhijun Cheng; Xiaoding Ma; Han Wu; Yanling Liu; Kunneng Zhou; Yilin Chen; Weiwei Ma; Jingcui Bi; Xin Zhang; Xiuping Guo; Jiulin Wang; et al. (Plant Cell Reports, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Phosphorus accumulation in grains of japonica rice as affected by nitrogen fertilizer - Junguo Bi; Zhenghui Liu; Zhaomiao Lin; Md A. Alim; Muhammad I. A. Rehmani; Ganghua Li; Qiangsheng Wang; Shaohua Wang; Yanfeng Ding (Plant and Soil, 2013)

Time-dependent regulation of neuregulin-1β/ErbB/ERK pathways in cardiac differentiation of mouse embryonic stem cells - Ming Chen; Lin-Lin Bi; Zhi-Quan Wang; Fang Zhao; Xue-Dong Gan; Yang-Gan Wang (Molecular and Cellular Biochemistry, 2013)

Full genome analysis of a novel type II feline coronavirus NTU156 - Chao-Nan Lin; Ruey-Yi Chang; Bi-Ling Su; Ling-Ling Chueh (Virus Genes, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Dynamic distribution and tissue tropism of infectious laryngotracheitis virus in experimentally infected chickens - Lin-Guo Wang; Jun Ma; Chun-Yi Xue; Wei Wang; Chao Guo; Feng Chen; Jian-Ping Qin; Ning-Hai Huang; Ying-Zuo Bi; Yong-Chang Cao (Archives of Virology, 2013)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Clinical Value of ELISA-MPT64 for the Diagnosis of Tuberculous Pleurisy - Zhonghua Liu; Changtai Zhu; Hua Yang; Haili Hu; Yonghong Feng; Lianhua Qin; Zhenling Cui; Aixiao Bi; Ruijuan Zheng; Ruiliang Jin; Lin Fan; Zhongyi Hu (Current Microbiology, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Salicylic acid-altering Arabidopsis mutants response to salt stress - Lin Hao; Yan Zhao; Dandan Jin; Ling Zhang; Xiaohua Bi; Hongxing Chen; Qiang Xu; Chunyan Ma; Guangzhe Li (Plant and Soil, 2012)

Shotgun proteomics and network analysis of ubiquitin-related proteins from human breast carcinoma epithelial cells - Jian Zhou; Deng Bi; Yong Lin; Ping Chen; Xianchun Wang; Songping Liang (Molecular and Cellular Biochemistry, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Phytoplankton variation and its relationship with the environment in Xiangxi Bay in spring after damming of the Three-Gorges, China - Guangjie Zhou; Xuemin Zhao; Yonghong Bi; Yubin Liang; Jianlin Hu; Min Yang; Yu Mei; Kongxian Zhu; Lin Zhang; Zhengyu Hu (Environmental Monitoring and Assessment, 2011)

H2S Protects Hippocampal Neurons from Anoxia–Reoxygenation Through cAMP-Mediated PI3K/Akt/p70S6K Cell-Survival Signaling Pathways - Jian-Lin Shao; Xiao-Hong Wan; Yan Chen; Chun Bi; Hong-Mei Chen; Ying Zhong; Xin-Hua Heng; Jin-Qiao Qian (Journal of Molecular Neuroscience, 2011)

Dynamic response of ginsenosides in American ginseng to root fungal pathogens - Xiao Lin Jiao; Wu Bi; Ming Li; Yong Luo; Wei Wei Gao (Plant and Soil, 2011)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Notes on the breeding biology of the Sichuan Treecreeper (Certhia tianquanensis) - Yue-Hua Sun; Ying-Xin Jiang; Jochen Martens; Zhong-Lin Bi (Journal of Ornithology, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Bifunctional oligo(ethylene glycol) decorated surfaces which permit covalent protein immobilization and resist protein adsorption - Xinyan Bi; Huan Xu; Siok Lian Lai; Kun-Lin Yang (Biofouling, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Partial characterization of a hydrophobin protein Po.HYD1 purified from the oyster mushroom Pleurotus ostreatus - Ai Min Ma; Lin Jun Shan; Hui Jie Wang; Zhao Ping Du; Bi Jun Xie (World Journal of Microbiology and Biotechnology, 2008)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

An interspecific somatic hybrid between Actinidia chinensis and Actinidia kolomikta and its chilling tolerance - Zun-an Xiao; Lin-chen Wan; Bi-wen Han (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)

Modelling the global monsoon system by IAP 9L AGCM - Xue Feng; Bi Xunqiang; Lin Yihua (Advances in Atmospheric Sciences, 2001)

Dependence of the agcm climatology on the method of prescribing surface boundary conditions and its climatological implication - Lin Zhaohui; Bi Xunqiang; Wang Huijun; Zeng Qingcun (Advances in Atmospheric Sciences, 1999)

Accumulation of Ag, Cd, Co, Cu, Hg, Ni and Pb in Pavlova viridis Tseng (Haptophyceae) - Bi-lian Chen; Qin Huang; Xiao-jian Lin; Qiao-qin Shi; Song-gang Wu (Journal of Applied Phycology, 1998)